Correlation of low birth pH with cognitive and language outcomes at two years - Abdelrahman, Khaled; Groteklaes, Anne; Demir, Sebiha; Jiménez Cruz, Jorge; Dresbach, Till; Mueller, Andreas; Sabir, Hemmen (Frontiers in Pediatrics, 2025)
BackgroundMild hypoxic-ischemic encephalopathy (HIE) often goes undected due to the narrow therapeutic window, subtle or absent clinical signs, and the lack of standardized diagnostic criteria. A broader umbilical cord blood pH threshold may help identifying at-risk neonates. Long-term developmental outcomes of term-born infants with isolated acidosis are lacking.ObjectiveTo examine the long-term non-verbal cognitive and language development at two years of term-born infants with an umbilical cord blood pH between 7.0 and 7.15 but no apparent clinical signs of mild HIE.Study designRetrospective observational study of 101 term-born infants. Developmental outcome was assessed using the Parent Report of Children's Abilities—Revised (PARCA-R) questionnaire for infants aged between 23 months and 27 months. Standardized PARCA-R scores are interpreted as follows: ≥85 = normal development, 70–84 = mild developmental delay, <70 = moderate developmental delay.ResultsPARCA-R Scores <85 in either non-verbal cognitive or language delay occurred in 39% of the cohort: 32% of them in non-verbal cognitive and 16% in language domain. No significant differences in developmental outcomes between the pH subgroups were found. Our outcomes were highly consistent with reported outcomes of infants diagnosed with mild HIE.ConclusionTerm-born infants with isolated perinatal acidosis may be at increased risk of developmental impairments at two years, despite being considered clinically healthy at birth.